Evaluation of Shrimp Head-Based Liquid Organic Fertilizer as a Sustainable Alternative Nutrient Source for Nannochloropsis sp. Culture - Kartina; Nurdahlia (Universitas Atma Jaya Yogyakarta, 2025)
Laboratory-scale Nannochloropsis sp. cultures typically rely on expensive commercial nutrients for aquaculture feed production. Shrimp head waste contains important nutrients that can be used to produce liquid organic fertilizers. This study aimed to evaluate the effect of using commercial fertilizer combined with liquid organic shrimp head fertilizer (LOF) on the growth of Nannochloropsis sp. on a controlled scale. The experimental design included four treatments (P0:100% commercial fertilizer), P1 (50% commercial + 50% LOF), P2 (75% commercial + 25% LOF), and P3 (100% LOF). Cell growth data were subjected to ANOVA and Duncan's tests. The use of LOF significantly influenced the growth of Nannochloropsis sp. on day 7. Peak growth occurred on day 7. P0 treatment (100% commercial fertilizer) showed the highest growth (15.7 × 104 cells/ml), although it was not statistically different from P1 (50% commercial + 50% LOF) and P2 (75% commercial + 25% LOF). The highest Specific Growth Rate was observed in the P0 treatment (0.22). This suggests that while shrimp head LOF alone may not be sufficient, its combination with commercial fertilizers holds promise for the sustainable cultivation of Nannochloropsis sp.